Microstructure and properties of hypoeutectic silumin treated by high-current pulsed electron beams - Ivanov, Yu.F.; Zagulyaev, D.V.; Nevskii, S.A.; Gromov, V.Е.; Sarychev, V.D.; Semin, A.P. (Успехи физики металлов, 2019)
The structural-phase states, microhardness, and tribological properties of hypoeutectic silumin after electron-beam treatment are studied by the methods of contemporary physical materials science. The object of the study is hypoeutectic АК10М2Н-type silumin containing 87.88 wt.% of Al and 11.1 wt.% of Si as the base components.